Sponsorship in International Sports Events: A Study of Sponsors' Perceptions of Congruence, Sincerity and Brand Exposure - Kautsar At-Thariq Prastijo; Mohammad Arif Ali; Tandiyo Rahayu; Gustiana Mega Anggita; Jeremy Christian Abadi (Universitas Negeri Semarang, 2025)
Sponsorship is an important part of global brands looking to increase participation and acceptance, especially through international sporting events such as the Tour de Borobudur 2023. This study aims to adds to the limited literature on sponsorship perspectives and offers practical implications for sports marketers, event organisers, and brand strategists looking to build meaningful and sustainable sponsorship partnerships, while addressing a gap in existing literature that has largely overlooked sponsor perspectives This study employed a descriptive quantitative research focused on the sponsors' perceptions of event-brand congruence, brand sincerity and brand exposure. Data was collected through a structured questionnaire administered to sponsoring organisations and analysed using descriptive statistics. The findings reveal that sponsors perceive a strong event-brand congruence, both in function and image, which enhances credibility and facilitates brand recall. Sincerity and brand authenticity are viewed as essential attributes that foster trust and shape stakeholders’ positive attitudes. Sponsors also place strong emphasis on sincerity, viewing authenticity and value alignment as essential for building trust and fostering emotional connections with audiences. Although brand exposure was perceived as moderate, sponsors expressed intentions to leverage future sponsorships to enhance visibility and reach. The results of this study showed a strong perception of functional and image congruence, indicating that consistency between sponsor and event can increase strategic value. Additionally, sponsors value honesty, seeking cooperation that reflects their brand's genuine values and helps build an emotional connection with the audience. Although current brand exposure levels were considered moderate, sponsors clearly intend to leverage future sponsorships to increase exposure, reflecting the principle of brand ubiquity.